Is Mas Selamat a rambo? - Desker, Barry (2016)
SINCE THE arrest of Mas Selamat on 1 April by the Malaysian Special Branch was revealed, we have been regaled by reports of his previous escapes from custody while under detention in Singapore and Indonesia.